2010
DOI: 10.1002/pssc.200983821
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular organization of chiral molecules on metallic surfaces: D‐alaninol on Cu(100) as a case study

Abstract: The adsorption configuration of a chiral amino alcohol, Dalaninol, on Cu(100) is studied with DFT ab‐initio calculations. We address the case of the formation of a self‐assembled monolayer that is experimentally found when depositing the molecule at room temperature. Preliminary calculations are performed for a cluster of four isolated molecules in gas phase, both at the MP2 and GGA‐DFT level. Further results deal with the adsorption on the copper surface. STM images of two candidates structures are simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The case of the isolated tetramer of D-alaninol molecules adsorbed on Cu(100) has been analyzed by MD starting from the most stable geometry found for the isolated tetramer through DFT optimization at 0 K. 40 The ED analysis 43 is shown in Figure 7a and reports the eigenvalues of the covariance matrix of all-atom positional fluctuations provided by 50 ns dynamics obtained at RT. The set of ortho-normal eigenvectors produced by covariance matrix diagonalization provides the set of directions along which the system undergoes either conformational transitions, i.e., eigenvectors showing larger eigenvalues, or high-frequency (nearly constrained) oscillations, i.e., small eigenvalues.…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case of the isolated tetramer of D-alaninol molecules adsorbed on Cu(100) has been analyzed by MD starting from the most stable geometry found for the isolated tetramer through DFT optimization at 0 K. 40 The ED analysis 43 is shown in Figure 7a and reports the eigenvalues of the covariance matrix of all-atom positional fluctuations provided by 50 ns dynamics obtained at RT. The set of ortho-normal eigenvectors produced by covariance matrix diagonalization provides the set of directions along which the system undergoes either conformational transitions, i.e., eigenvectors showing larger eigenvalues, or high-frequency (nearly constrained) oscillations, i.e., small eigenvalues.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…DFT calculations on an isolated tetrameric structure in gas phase have been validated by MP2 calculations. 40 MD calculations, performed using Gromacs packages, 41 have been carried out, modeling the Cu(100) surface by a three-layer copper slab containing 42 Cu atoms per layer for adsorbed isolated D-alaninol tetramer and 378 Cu atoms per layer for an adsorbed cluster composed of nine tetramers (3 Â 3 matrix); no periodic boundary conditions have been imposed. The interaction between molecules and surface was modeled using the results of DFT calculations for the adsorption of a single Dalaninol molecule on Cu(100) 35,36 where nitrogen is covalently bonded with copper atoms on top.…”
Section: ' Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27] Alaninol is a small and conformationally flexible bifunctional chiral amino-alcohol belonging to a group of molecules that are important industrial precursors or intermediates for the synthesis of pharmaceutical compounds. 28 It is known that D-alaninol and L-alaninol adsorbed on Cu (100) surface form an ordered self-assembled chiral saturated monolayer.…”
mentioning
confidence: 99%
“…In previous works, Density Functional Theory (DFT) and classical Molecular Dynamics (MD) were employed to interpret experimental evidence in STM, XPS, and LEED spectroscopies; here it has been shown that d -alaninol forms tetrameric clusters at low coverages and an extremely ordered monolayer made of tetrameric units at high coverages. d -Alaninol tetrameric units are aligned along an axis which is rotated by 14° with respect to the [011] direction of the underlying Cu lattice.…”
Section: Introductionmentioning
confidence: 99%